Mapping of Spring Discharge into Lake Altoona. - Fairbairn, David J.; Teige, Emilia L. (My University, 2009)
Lake Altoona is located in the Northeast section of the city of Altoona. It is approximately 800 acres in area (~3.24Km2) and has its own community surrounding it. The purpose of this study is to better understand the sources of pollution into the lake. Large algae blooms serve as evidence for excess nutrients entering the lake. Though the majority of the nutrient pollution is suspected from non-point source agriculture run off entering the lake from the Eau Claire River, a portion could be contributed to domestic sources; such as leaking septic systems.
Color poster with text, images, and maps describing research conducted by Emilia Tiege and David J. Fairbairn, advised by Bianca Pedersen.
Keywords: Posters; Altoona, Lake (Wis.)--Environmental conditions; Water pollution--Wisconsin--Altoona, Lake; Runoff--Wisconsin--Altoona, Lake; Urban runoff--Wisconsin--Altoona, Lake